Analysis of urban sustainable development perceptions in the City of Jyväskylä : a qualitative case study on Resource Wisdom concept - Sohlman, Margarita (2021)
Due to urbanization and population growth cities are facing sustainability challenges. The amount of people living in urban areas in Finland is estimated to rise to 82 % by the end of 2050. To deal with these current and future problems cities must be innovative and find new solutions and create a robust roadmap to achieve strategic goals and sustainable solutions. This case study focuses on Resource Wisdom and sustainability concepts perceptions and how these are put into practice in Koas and the City of Jyväskylä. The conceptual framework is divided into three sections, sustainable city, smart city, and urban resilience.